Data from: Genetic stock structure of Anadromous Arctic char in Canada's Central Arctic: potential implications for the management of Canada's largest Arctic char commercial fishery - Harris, Les N.; Moore, Jean-Sébastien; Bajno, Robert; Tallman, Ross F. (Zenodo, 2017)
The Arctic Char Salvelinus alpinus is widely considered the most important subsistence fish species in the Canadian Arctic. Throughout the species' range, commercial fisheries for Arctic Char also exist, the management of which primarily follows river-specific harvest strategies. Such an approach, however, may not be appropriate if the management unit or stock does not accurately reflect a demographically independent population or if mixtures of populations are being harvested. We assayed microsatellite DNA variation among 744 Arctic Char from the Cambridge Bay region, Nunavut, where the largest commercial fishery for the species exists, in order to identify the most appropriate spatial scale at which these stocks should be managed. Our sampling design specifically mirrored that of the commercial fishery in order to describe patterns of genetic structure and genetic variation within and among the harvested component. We also included Arctic Char from more geographically distant sampling locations to provide a spatial context for genetic stock structuring in the region. Overall, we found moderate but significant structure across the entire study area. In contrast, commercially harvested stocks were weakly differentiated, especially among the stocks that are considered part of the Wellington Bay complex. We propose several hypotheses for this weak differentiation, including (1) our sampling design that mirrored the commercial harvest, (2) high rates of potential gene flow, and (3) large effective population sizes. Our results may have important implications for commercial and subsistence fisheries management, including the notion that there are several potential units of conservation below the species level. Microsatellite data Genepop file (3 digit format) containing all microsatellite data. Population names are listed in Table 1 of the paper. Genepop 3 Digit